PENERAPAN MODEL PEMBELAJARAN KOOPERATIF STRATEGI SPOTLIGHT UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF FISIKA SISWA KELAS VIII SMPN 8 PEKANBARU - Karmila, Neneng; Ma?ruf, Zuhdi; M. Nor, M. Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this research is to investigate the improvement of physic achievement in physic learning by using spotlight strategy. Intact group comparison design has been used to find out the differentiate of physic achievement of both group, experiment group and control group. There were 77 students of SMPN 8 Pekanbaru, class VIII that devide into two group, experiment and control have been participated in this research. The physic achievement test that consist of 20 items with multiple choice type was used. This instrument measure the physic achievement from C1 (knowledge) to C4 (analyze) of Bloom Tacsonomy. The descriptive analysis found that physic achievement of students in spotlight strategy learning is higher than conventional learning. The T-tes analysis showed that the differentiate of physic achievement of students was significant at 0,05 level.Key words: Physic Achievement, Physic Learning, Spotlight Strategy